KEEFEKTIFAN PENGGUNAAN SOFTWARE MACROMEDIA FLASH DALAM PEMBELAJARAN BERCERITASISWA KELAS 1 SD INPRES HARTACO INDAH MAKASSAR - Nur Hafsah Yunus MS (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2014)
The effectiveness of macromedia flash software in storytelling learning of the first grade students at SD Inpres Hartaco Indah Makassar aimed to describe the effectiveness of macromedia flash software in learning storytelling of the first grade students of SD Inpres Hartaco Indah Makassar. This study used an experimental research design with posttest only control design. The population of this study is the first elementary grade students at SD Inpres Hartaco Indah. The sample was two classes that each class has 25 students, so the total sample size was 50 students., class IA as a control group and class IB as the experimental group. Sampling was chosed by employing cluster random sampling. The techniques used to collect data were tests and observation. The test was in the form of storytelling and the data collected were analiyzed using descriptive statistical techniques and inferential statistical parametric T- Test genius that is processed by the computer program SPPS version 18 windows. Results of hypothesis testing show that the coefficient of tcount is 3.374 and on the significant level 95%, it was found that ttable (2.02). Thus, tcount is greater than ttable then H0 is rejected and H1 is accepted. Therefore, it can be concluded that there is a significant difference between the students’ score on pretest and posttest in the experimental group. In addition, the uses of macromedia flash is more effective to be used in storytelling learning at elementary students in class I Hartaco Indah Makassar.